Gemcabene, a First-in-Class Hypolipidemic Small Molecule in Clinical Development, Attenuates Osteoarthritis and Pain in Animal Models of Arthritis and Pain - Srivastava, Rai A. K.; Cornicelli, Joseph A.; Markham, Bruce; Bisgaier, Charles L. (Frontiers in Pharmacology, 2018)
Our clinical studies have demonstrated that gemcabene, a small molecule in late-stage clinical development, lowers pro-inflammatory acute-phase protein, C-reactive protein (CRP). This observation was further confirmed in a cell-based study showing inhibition of cytokine-induced CRP production. Based on these observations, in the present study, we tested the hypothesis that gemcabene may possess anti-inflammatory activities in animal models of inflammatory disease. Efficacy of gemcabene was investigated in rat models of carrageenan-induced thermal hyperalgesia (CITH), monosodium iodoacetate (MIA)-induced osteoarthritis (OA), and IL-6/IL-6sR-induced inflammation. We also evaluated efficacy of gemcabene in collagen antibody-induced joint swelling and arthritis in BALB/c mice. In CITH rat model, gemcabene administration attenuated paw withdrawal latency (60% at 30 mg/kg/d and 97% at 100 mg/kg/d) and showed improvement in joint swelling (-50% at 30 mg/kg/d) in MIA model of osteoarthritis. These findings were further corroborated by IL-6/IL-6sR knee injection model in rat, showing 63 and 71% reduction in hind paw weight distribution at 10 and 30 mg/kg/d doses, respectively. In mouse model of monoclonal antibody–induced arthritis, a dose-dependent attenuation of joint swelling was observed. These results demonstrate that the anti-inflammatory activity of gemcabene previously observed in cell-based and in clinical studies also occurred in animal models of inflammation-induced arthritis and hyperalgesia. Thus, in addition to hypolipidemic efficacy, the anti-inflammatory activity of gemcabene may have additional benefits to patients with elevated vascular inflammation.